2021
DOI: 10.1002/ccr3.3925
|View full text |Cite
|
Sign up to set email alerts
|

Statin‐associated necrotizing autoimmune myopathy with concurrent myasthenia gravis

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 18 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…Autoimmune necrotizing myositis [10][11][12]138] is a feared complication of statin use. (Other autoimmune complications of statins are also reported [139][140][141][142][143]-which can affect muscle [144][145][146][147]-and in some cases, these accompany autoimmune myositis [13][14][15][16]148].) Autoimmunity is also a complication of COVID-19 [149][150][151][152] (encompassing, specifically, autoimmune conditions reported with statins [6,7,[153][154][155] including necrotizing myositis [8,9]) and is a factor in long-COVID [156][157][158][159]: in one "multi-omics" study of long-COVID, an autoimmune profile represented one of the four key patterns observed [160].…”
Section: Skeletal Muscle (Airway Dilator Muscles and Muscles Of Respi...mentioning
confidence: 99%
See 1 more Smart Citation
“…Autoimmune necrotizing myositis [10][11][12]138] is a feared complication of statin use. (Other autoimmune complications of statins are also reported [139][140][141][142][143]-which can affect muscle [144][145][146][147]-and in some cases, these accompany autoimmune myositis [13][14][15][16]148].) Autoimmunity is also a complication of COVID-19 [149][150][151][152] (encompassing, specifically, autoimmune conditions reported with statins [6,7,[153][154][155] including necrotizing myositis [8,9]) and is a factor in long-COVID [156][157][158][159]: in one "multi-omics" study of long-COVID, an autoimmune profile represented one of the four key patterns observed [160].…”
Section: Skeletal Muscle (Airway Dilator Muscles and Muscles Of Respi...mentioning
confidence: 99%
“…Such AEs include, but are not limited to, muscle pain, muscle weakness, and fatigue. Rhabdomyolysis and autoimmune necrotizing myositis specifically have occurred with COVID-19 [6][7][8][9] as they can occur with statins [10][11][12][13][14][15][16]. Based on these and other considerations, the risk side of the risk-benefit ratio should also be considered seriously in deliberations about statin use.…”
Section: Introductionmentioning
confidence: 99%